Robust In Vitro and In Vivo Immunosuppressive and Anti-inflammatory Properties of Inducible Caspase-9-mediated Apoptotic Mesenchymal Stromal/Stem Cell. (3rd March 2022) - Romecín, Paola Alejandra; Vinyoles, Meritxell; López-Millán, Belén; de la Guardia, Rafael Diaz; Atucha, Noemi M; Querol, Sergi; Bueno, Clara; Benitez, Raquel; Gonzalez-Rey, Elena; Delgado, Mario; Menéndez, Pablo
Abstract: Mesenchymal stromal stem/cells (MSC) therapies are clinically used in a wide range of disorders based on their robust HLA-independent immunosuppressive and anti-inflammatory properties. However, the mechanisms underlying MSC therapeutic activity remain elusive as demonstrated by the unpredictable therapeutic efficacy of MSC infusions reported in multiple clinical trials. A seminal recent study showed that infused MSCs are actively induced to undergo apoptosis by recipient cytotoxic T cells, a mechanism that triggers in vivo recipient-induced immunomodulation by such apoptotic MSCs, and the need for such recipient cytotoxic cell activity could be replaced by the administration of ex vivo-generated apoptotic MSCs. Moreover, the use of MSC-derived extracellular vesicles (MSC-EVs) is being actively explored as a cell-free therapeutic alternative over the parental MSCs. We hypothesized that the introduction of a "suicide gene" switch into MSCs may offer on-demand in vivo apoptosis of transplanted MSCs. Here, we prompted to investigate the utility of the iCasp9/AP1903 suicide gene system in inducing apoptosis of MSCs. iCasp9/AP1903-induced apoptotic MSCs (MSC iCasp9+ ) were tested in vitro and in in vivo models of acute colitis. Our data show a very similar and robust immunosuppressive and anti-inflammatory properties of both "parental" alive MSC GFP+ cells and apoptotic MSC iCasp9+ cells in vitro and in vivo regardless of whether apoptosis was induced in vivo or in vitro before administering MSC iCasp9+ lysates. This development of an efficient iCasp9 switch may potentiate the safety of MSC-based therapies in the case of an adverse event and, will also circumvent current logistic technical limitations and biological uncertainties associated to MSC-EVs. Graphical Abstract: